Pharmacological modulation of metabotropic glutamate receptor subtype 5 and 7 impairs extinction of social fear in a time-point-dependent manner - Slattery, David A.; Neumann, Inga D.; Flor, Peter J.; Zoicas, Iulia (Behavioural Brain Research, 2017)
Pharmacological modulation of metabotropic glutamate receptor subtype 5 (mGluR5) and 7 (mGluR7) was shown to attenuate the acquisition and to facilitate the extinction of cued and contextual, non-social, fear. Using the allosteric mGluR5 antagonist 2-methyl-6-(phenylethynyl)-pyridine (MPEP) and the allosteric mGluR7 agonist N,N'-dibenzyhydryl-ethane-1,2-diamine dihydrochloride (AMN082), we aimed to study how pharmacological blockade of mGluR5 and activation of mGluR7 influence acquisition and extinction of social fear in mice. We could show that when administered before social fear conditioning, neither MPEP nor AMN082 affected acquisition and extinction of social fear, suggesting that mGluR5 inactivation and mGluR7 activation do not alter social fear. However, when administered before social fear extinction, both MPEP and AMN082 impaired social fear extinction and extinction recall. These findings suggest that mGluR5 inactivation and mGluR7 activation are unlikely to prevent the formation of traumatic social memories. Furthermore, medication strategies aimed at augmenting exposure-based therapies for psychiatric disorders associated with social deficits via modulation of mGluR5 and mGluR7 must be pursued cautiously because of their potential to delay social fear extinction processes.
EVALuna2:33577